Processes in Doping System: Quantification Reports in Mixed Martial Arts Fighters - Del-Aguila-Arcentales, Shyla (2022)
Mixed martial arts (MMA) has always been surrounded by controversy due to the unusual muscle development of its participants, so it is crucial to know the strategies that have been implemented to reduce doping cases. The main purpose of this paper is to describe the various cases of doping detected by USADA in UFC MMA participants. In addition, strategies that are being developed to reduce cases of positive doping are proposed. From the UFC USADA database, doping cases were extracted, obtaining the substance or substances involved; the formula, physiological effect and the athletes involved; the dates of the sampling; if it was out of competition or in-competition and the sanction time. The substances that were most involved were found to be Ostarine (22), Clomiphene (9), Diuretics (10) and Stanozolol (9). Some sanctions were diminished because they were treated with contamination of supplements (cases of Ostarine) and cases of contamination of meat (Clomiphene). When contaminated supplements were reported, they were added to the list of high-risk supplements maintained as part of USADA’s online dietary supplement safety education and awareness resource—Supplement 411. There were also cases in which positive doping could be avoided through the early report of therapeutic use exemptions. The methodology that the USADA has implemented allows us to register the athletes with positive doping, check the risk of the supplements before being bought and provide a teaching portal. These efforts are necessary to implement in all countries in which MMA is practiced, avoiding the participation of doped martial artists.